The need for intergrating spirituality with psychology and professional ethics in counseling: a lay counseling case study - "Kamau, Patriciah" (Nairobi)
Includes bibliographical references
Keywords: COUNSELING;SPIRITUALITY AND COUNSELING;COUNSELING-GOALS;COUNSELING-METHODS;SIMPLISTIC BELIEFS;PROFESSIONAL ETHICS